Aloin induced apoptosis by enhancing autophagic flux through the PI3K/AKT axis in osteosarcoma - Jiaming He; Wenkan Zhang; Xiaozhong Zhou; Weiqi Yan; Zhan Wang (BMC, 2021)
Abstract Background Osteosarcoma is a malignant tumor of bone and soft tissue in adolescents. Due to its tumor biological behavior pattern, osteosarcoma usually generates poor prognosis. Autophagy is an important self-defense mechanism in osteosarcoma. Methods Cell viability in IC50 testing and reverse assays was examined by the MTT assay. Cell apoptosis conditions were examined by flow cytometry, Hoechst 33,342 staining and apoptosis-related protein immunoblotting. Autophagy conditions were tested by autophagy-related protein immunoblotting, transmission electron microscopic observation and dual fluorescence autophagy flux detection. The possible targets of aloin were screened out by network pharmacology and bioinformatic methods. Osteosarcoma xenografts in nude BALB/c mice were the model for in vivo research on tumor suppression, autophagy induction, pathway signaling and toxicity tests. In vivo bioluminescence imaging systems, immunohistochemical assays, and gross tumor volume comparisons were applied as the main research methods in vivo. Results Aloin induced osteosarcoma apoptosis in a dose-dependent manner. Its possible effects on the PI3K/AKT pathway were screened out by network pharmacology methods. Aloin increased autophagic flux in osteosarcoma by downregulating the PI3K/AKT pathway. Aloin promoted autophagic flux in the osteosarcoma cell lines HOS and MG63 in a dose-dependent manner by promoting autophagosome formation. Chloroquine reversed the apoptosis-promoting and autophagy-enhancing effects of aloin. Autophagy induced by starvation and rapamycin significantly enhanced the autophagic flux and apoptosis induced by aloin, which verified the role of the PI3K/AKT axis in the pharmacological action of aloin. Therapeutic effects, autophagy enhancement and regulatory effects on the PI3K/AKT/mTOR pathway were demonstrated in a nude mouse xenogeneic osteosarcoma transplantation model. Conclusions Aloin inhibited the proliferation of osteosarcoma by inhibiting the PI3K/AKT/mTOR pathway, increasing autophagic flux and promoting the apoptosis of osteosarcoma cells.